(untitled) (Annals of Medical Research, 2023)
Aim: This study aims to investigate the impact of von Mises stress distribution on the cervical spine and soft tissue of the neck at different flexion angles of 0°, 15°, 30°, 45°, and 60°. Materials and Methods: Finite element analysis of the neck’s cervical spine and soft tissue was performed separately in Ansys Discovery Live software, a possible approach for simulating the mechanical behavior of the neck. Three-dimensional (3D) models were created in 3D Max software and static structural analyses of soft tissues were performed in ANSYS by using the Finite Element Method. The maximum stress distributions of the cervical spine in cervical vertebra bodies at different flexion angles were analyzed at the lowest and highest stress values of 0° and 30°, respectively. For the intervertebral contact surfaces, the lowest and highest stress values were determined at 0° and 45°, respectively. Results: The value of stress showed a linear increase with increasing flexion angles in the soft tissue of the neck. The observation that the stress values obtained at different flexion angles were arbitrarily in either positive or negative directions when compared to the upright posture suggests that the effect of neck flexion on stress distribution in the cervical spine is complex and multifactorial. The change in stress values in the soft tissue of the neck was always positive and linear with increasing flexion angles. Conclusion: People who work with technological devices are prone to a musculoskeletal disorder associated with forward flexion of the neck, and individuals are encouraged to adopt a neck flexion angle between 0° and 15°. This finding could help guide the development of strategies to reduce the risk of neck injury or damage in different postures.